Diagnostic Sequences That Distinguish M. avium Subspecies Strains - Bannantine, John P.; Stabel, Judith R.; Bayles, Darrell O.; Conde, Cyril; Biet, Franck (Frontiers in Veterinary Science, 2021)
Over a decade ago Mycobacterium avium subspecies paratuberculosis (Map) specific genes were initially identified in a whole genome context by comparing draft genome sequences of Map strain K-10 with Mycobacterium avium subspecies hominissuis (Mah) strain 104. This resulted in identification of 32 Map specific genes, not including repetitive elements, based on the two-genome comparison. The goal of this study was to define a more complete catalog of M. avium subspecies-specific genes. This is important for obtaining additional diagnostic targets for Johne’s disease detection and for understanding the unique biology, evolution and niche adaptation of these organisms. There are now over 28 complete genome sequences representing three M. avium subspecies, including avium (Maa), Mah and Map. We have conducted a comprehensive comparison of these genomes using two independent pan genomic comparison tools, PanOCT and Roary. This has led to the identification of more than 250 subspecies defining genes common to both analyses. The majority of these genes are arranged in clusters called genomic islands. We further reduced the number of diagnostic targets by excluding sequences having high BLAST similarity to other mycobacterial species recently added to the National Center for Biotechnology Information database. Genes identified as diagnostic following these bioinformatic approaches were further tested by DNA amplification PCR on an additional 20 M. avium subspecies strains. This combined approach confirmed 86 genes as Map-specific, 7 as Maa-specific and 3 as Mah-specific. A single-tube PCR reaction was conducted as a proof of concept method to quickly distinguish M. avium subspecies strains. With these novel data, researchers can classify isolates in their freezers, quickly characterize clinical samples, and functionally analyze these unique genes.